Quality of medical advice for chronic pain on social platforms. Issue 1 (18th October 2019) - Costello, Kaitlin Light
ABSTRACT: Chronic pain is a stigmatized condition, and many patients report that it is difficult to get information from healthcare providers. As a result, some patients go online to exchange health information on social platforms, but the type and quality of this information is unknown. In this mixed‐methods study, comments on a chronic pain platform were inductively analyzed and a typology of medical advice was developed. Subsequently, the alignment of this advice with evidence in the medical literature was assessed by systematically searching for relevant systematic reviews or meta‐analyses. Five types of advice were present: over‐the‐counter remedies, prescription drugs, illicit substances, seeing a different healthcare provider, and lifestyle changes. No evidence was available for 33.9% of the advice, but 33% had at least low support in the literature. 7.8% was harmful. Contributions from this study include a general typology of medical advice online, a methodological approach for assessing the quality of such advice, and several recommendations for future research.